2003
DOI: 10.1508/cytologia.68.389
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Characterization of <i>Astyanax</i> sp B (Characidae, Tetragonopterinae), an Endemic Species of the Iguaçu River, Paraná, Brazil

Abstract: Summary Cytogenetics studies on Astyanax sp B, an endemic species of the Iguaçu River (Paraná, Brazil) were carried out. The specimens showed a standard diploid number of 2nϭ50 chromosomes with a karyotype consisting of 6 metacentric, 24 submetacentric, 6 subtelocentric and 14 acrocentric chromosomes. In addition to the basic karyotype, all the specimens presented 1-2 supranumerary or B chromosomes in mitotic metaphases. Three morphological types of B chromosomes have been identified in population under analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…Ne´o, Bertollo and Moreira-Filho (2000) and Ferro, Moreira-Filho and Bertollo (2003) also detected other types of B chromosomes in Astyanax scabripinnis. Fazoli et al (2003) also found three morphological types of B chromosomes in Astyanax sp. B from the River Iguac¸u: a metacentric macrochromosome slightly smaller than the first pair of the chromosome complement, a small submetacentric and an acrocentric-type microchromosome.…”
Section: Discussionmentioning
confidence: 78%
“…Ne´o, Bertollo and Moreira-Filho (2000) and Ferro, Moreira-Filho and Bertollo (2003) also detected other types of B chromosomes in Astyanax scabripinnis. Fazoli et al (2003) also found three morphological types of B chromosomes in Astyanax sp. B from the River Iguac¸u: a metacentric macrochromosome slightly smaller than the first pair of the chromosome complement, a small submetacentric and an acrocentric-type microchromosome.…”
Section: Discussionmentioning
confidence: 78%
“…C (Kantek et al, 2003), Astyanax sp. B (Fazoli et al, 2003) and Astyanax altiparanae (Cenci and Margarido, 2003;Kantek et al, 2004) from the Iguaçu river, these species were clearly distinguishable by their cytogenetic features, showing the probable lack of gene flow between them as well as the importance of karyotypic data for the taxonomy of this fish group.…”
Section: Discussionmentioning
confidence: 99%
“…D did not differ from those of most species of this genus, including A. scabripinnis (Moreira-Filho and Bertollo 1991;Maistro et al, 1998;Souza et al, 1996), Astyanax sp.C (Kantek et al, 2003), Astyanax sp.B (Fazoli et al, 2003) and A. altiparanae (Cenci and Margarido, 2003;Kantek et al, 2004). The C-banding pattern could be considered equilocal on the chromosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such reduced amount of heterochromatin is also observed in other species of this genus, such as A. parahybae (Centofante et al, 2003), Astyanax sp. B (Fazoli et al, 2003), A. altiparanae (Fernandes & Martins-Santos, 2004), and A. jacuhiensis (Pacheco, pers. comm.).…”
Section: Discussionmentioning
confidence: 99%